Impact of tumor cell cytoskeleton organization on invasiveness and migration: a microchannel-based approach. - Claudio G Rolli; Thomas Seufferlein; Ralf Kemkemer; Joachim P Spatz (PLoS ONE, 2010)
Cell migration is a fundamental feature of the interaction of cells with their surrounding. The cell's stiffness and ability to deform itself are two major characteristics that rule migration behavior especially in three-dimensional tissue. We simulate this situation making use of a micro-fabricated migration chip to test the active invasive behavior of pancreatic cancer cells (Panc-1) into narrow channels. At a channel width of 7 microm cell migration through the channels was significantly impeded due to size exclusion. A striking increase in cell invasiveness was observed once the cells were treated with the bioactive lipid sphingosylphosphorylcholine (SPC) that leads to a reorganization of the cell's keratin network, an enhancement of the cell's deformability, and also an increase in the cell's migration speed on flat surfaces. The migration speed of the highly deformed cells inside the channels was three times higher than of cells on flat substrates but was not affected upon SPC treatment. Cells inside the channels migrated predominantly by smooth sliding while maintaining constant cell length. In contrast, cells on adhesion mediating narrow lines moved in a stepwise way, characterized by fluctuations in cell length. Taken together, with our migration chip we demonstrate that the dimensionality of the environment strongly affects the migration phenotype and we suggest that the spatial cytoskeletal keratin organization correlates with the tumor cell's invasive potential.